2013
DOI: 10.1007/s12663-013-0502-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Pattern of Maxillofacial Trauma Due to Road Traffic Accidents: A Prospective Study

Abstract: Background The incidence and causes of road traffic accidents (RTAs) vary with geographical location, socioeconomic status, religion and era. The etiological factors and associated injury patterns may be important in planning for preventive measures and treatment planning. The aim of this study was to evaluate and analyze the etiological factors, patterns and the frequency of maxillofacial injuries due to RTAs. Materials and Methods This prospective study was conducted on 350 patients with facial trauma due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 6 publications
5
61
1
1
Order By: Relevance
“…Agnihotri et al22 reported that the rate of RTA was increased on weekends due to an increase in the number of drivers who were under the influence of alcohol. In our study, 41.6% (111/267) of males were under the influence of alcohol at the time of injury.…”
Section: Discussionmentioning
confidence: 99%
“…Agnihotri et al22 reported that the rate of RTA was increased on weekends due to an increase in the number of drivers who were under the influence of alcohol. In our study, 41.6% (111/267) of males were under the influence of alcohol at the time of injury.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the literature concludes with the fact that the incidence of road traffic accidents is comparatively more in males than in females. [6,8,12,13,17,18,20,23,24,25,26] In a country like Saudi Arabia, females are prohibited from driving by law.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[5] The incidence and causes of road traffic accidents vary with geographical location, socioeconomic status, religion and era. [6] The incidence of traffic accidents is high in Saudi Arabia. Age of the driver, education level, profession, violation record, vehicle ownership, joy riding, poor eye sight, sun haze, sand storm, long hours driving, non-observance of speed limit, emerging and exiting from roads without signals, presence of stray animals, non-marking of the road, nonfamiliarity with the road, lack of regular checking of vehicles, lack of regular servicing of vehicles and driving under medication are factors associated with high incidence of road traffic accidents in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…
The mid-face is composed of: two maxillary bones, two nasal bones, two palatine bones, two zygomatic bones, two zygomatic process of temporal bone, two lacrimal bones, two inferior conchae and pterygoid plates of sphenoid, vomer, ethmoid and its attached conchae (2) .Fracture pattern may vary with behavior of injury, anatomy of the site of injury and direction of the affected impact force (3) .
ABSTRACTIntroduction: Mid face trauma, with or without life threatening injuries needs accurate assessment which should be in a systematic and repeated manner.Aim of the work: Is the identification of such injuries and the definitive management of common injury patterns that were changes laterally due to the advancement and severity of social life style.Patients and Methods: the study performed from January 2016 to December 2018 (36 months) on 288 adult patients with mid-face trauma, atResults: Patients demographic data demonstrated that road traffic accident, motor vehicle, is the major etiological factor that change the pattern of mid-face fractures due to change of economic and social life style.
Conclusion:The rapid change of the economic and social life style was reported as the leading cause of pattern change of mid-face trauma. RTAs were the main cause of fractures followed by falls and sport respectively.
KEYWORDS:Mid-face fracture, change the pattern of fracture, road traffic accident, modification of Le Fort fracture.(3324) Hala R. Ragab E.D.
…”
mentioning
confidence: 99%
“…The mid-face is composed of: two maxillary bones, two nasal bones, two palatine bones, two zygomatic bones, two zygomatic process of temporal bone, two lacrimal bones, two inferior conchae and pterygoid plates of sphenoid, vomer, ethmoid and its attached conchae (2) .…”
mentioning
confidence: 99%